YOUMARES 9 - The Oceans: Our Research, Our Future 2019
DOI: 10.1007/978-3-030-20389-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Microplastics Affect Marine Biota on the Cellular Level Is Important for Assessing Ecosystem Function: A Review

Abstract: Plastic has become indispensable for human life. When plastic debris is discarded into waterways, these items can interact with organisms. Of particular concern are microscopic plastic particles (microplastics) which are subject to ingestion by several taxa. This review summarizes the results of cutting-edge research about the interactions between a range of aquatic species and microplastics, including effects on biota physiology and secondary ingestion. Uptake pathways via digestive or ventilatory systems are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 228 publications
(335 reference statements)
0
32
1
Order By: Relevance
“…Until now, several laboratory studies demonstrated transfer of plastic particles in low-tier food chains, however, whole system trophic transfers require further investigation [ 98 , 99 ]. For further information regarding trophic level transfers of MPs/NPs, we refer readers to Prinz et al [ 6 ] and Prokić et al [ 7 ] who provided detailed overview on this topic.…”
Section: Individual and Population Adverse Outcomes Triggered By Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, several laboratory studies demonstrated transfer of plastic particles in low-tier food chains, however, whole system trophic transfers require further investigation [ 98 , 99 ]. For further information regarding trophic level transfers of MPs/NPs, we refer readers to Prinz et al [ 6 ] and Prokić et al [ 7 ] who provided detailed overview on this topic.…”
Section: Individual and Population Adverse Outcomes Triggered By Micrmentioning
confidence: 99%
“…The number of studies addressing MP/NPs toxicity is rapidly increasing, with focus on polyethylene (PE), polystyrene (PS) and polyvinyl chloride (PVC) which have the highest production and utilization among many species of plastic materials [ 1 ]. Rising interest in investigations of MP/NPs is likely related to their ability to translocate through biological barriers while at the same time maintaining large surface/mass ratio, as well as their potential to accumulate in the higher trophic level organisms via the food chain [ 6 , 7 ]. It is therefore of high interest of research and regulatory community to evaluate potential ecological as well as human health hazards of MPs/NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, high-density particles sink and accumulate in the sediment, while low-density particles float at the sea surface. However, due to their small dimensions, microplastics are easily available for uptake to a wide range of marine organisms [ 27 , 28 ]. This reduction in size not only impairs the cleanliness of the waters, but also causes some marine animals death due to ingestion.…”
Section: Plastics Microplastics and Their Impact In The Ecosystemmentioning
confidence: 99%
“…Microplastics have been found in almost every marine habitat and their ingestion has effects on marine and freshwater organisms, either as a consequence of their physical penetration, leaching of chemical additives or infection caused by microbial communities on microplastics (Prinz and Korez, 2020). Moreover, microplastics can be transferred to higher trophic levels in the food web (Lusher, 2015), thus sustaining and multiplying their detrimental effects.…”
Section: Introductionmentioning
confidence: 99%